The Passive Personality Principle In International Criminal Law And Syria - ده آبادي, محمد علي حاجي; شربو, نور الدين (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Many countries have adopted the passive personality principle, which is one of the important principles in international criminal law and included it in their laws, while this principle has not been explicitly accepted in the Syrian Penal Code despite the presence of a sign indicating the possibility of this and was mentioned in paragraph 1 of Article 18. The Syrian legislator’s acceptance of the principle under consideration does not contradict with the decisions of international criminal law, as the principle is an extension of those decisions and a guarantee of their achievement. In addition, it appears that rejecting the principle and not saying it leads to the Syrian legislator moving away from granting the necessary criminal protection to the Syrian nationals victims abroad, as this may contradict the national interests and benefits of the Syrian state.